Implementation of Zero Food Waste in the Buffet Restaurant Service (Case Study: Sheraton Grand Jakarta Hotel) - Nabila Hasna; Lilis Sulandari; Ila Huda Puspita Dewi; Mafisa Restami (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
This study is motivated by the growing issue of food waste in the hospitality industry, particularly in buffet services, which are characterized by large-scale food production. It aims to analyze the factors causing food waste and to implement the zero food waste concept in buffet restaurant services at Sheraton Grand Jakarta Hotels. The research method is a descriptive qualitative approach, employing observation, interviews, and documentation. The informants in this study include the Chef de Cuisine, Chef de Partie Hot Kitchen, and Chef de Partie Pastry Bakery. The results show that food waste is influenced by operational factors, inventory system factors, and hotel quality standards and regulations. Zero food waste is implemented through the stages of planning and production, serving, monitoring, and reuse and redistribution. The efforts include using occupancy data, implementing batch cooking, controlling serving container size, a gradual refill system, recording waste logs, and collaborating with external organizations to redistribute surplus food that is still suitable for consumption. In conclusion, the implementation of zero food waste has been carried out systematically and in an integrated manner. Keywords: Zero Food Waste, Buffet Service, Sheraton Grand Jakarta Hotels